Functional roles of complexin3 and complexin4 at mouse photoreceptor ribbon synapses - Babai, Norbert; Sendelbeck, Anna; Regus-Leidig, Hanna; Fuchs, Michaela; Mertins, Jasmin; Reim, Kerstin; Brose, Nils; Feigenspan, Andreas; Brandstätter, Johann Helmut (The Journal of Neuroscience, 2016)
Complexins (Cplxs) are SNARE complex regulators controlling the speed and Ca sensitivity of SNARE-mediated synaptic vesicle fusion. We have shown previously that photoreceptor ribbon synapses in mouse retina are equipped with Cplx3 and Cplx4 and that lack of both Cplxs perturbs photoreceptor ribbon synaptic function; however, Cplx3/4 function in photoreceptor synaptic transmission remained elusive. To investigate Cplx3/4 function in photoreceptor ribbon synapses, voltage-clamp recordings from postsynaptic horizontal cells were performed in horizontal slice preparations of Cplx3/4 wild-type (WT) and Cplx3/4 double knock-out (DKO) mice. We measured tonic activity in light and dark, current responses to changes in luminous intensity, and electrically evoked postsynaptic responses. Cplx3/4 decreased the frequency of tonic events and shifted their amplitude distribution to smaller values. Light responses were sustained in the presence of Cplx3/4, but transient in their absence. Finally, Cplx3/4 increased synaptic vesicle release evoked by electrical stimulation. Using electron microscopy, we quantified the number of synaptic vesicles at presynaptic ribbons after light or dark adaptation. In Cplx3/4 WT photoreceptors, the number of synaptic vesicles associated with the ribbon base close to the release site was significantly lower in light than in dark. This is in contrast to Cplx3/4 DKO photoreceptors, in which the number of ribbon-associated synaptic vesicles remained unchanged regardless of the adaptational state. Our results indicate a suppressing and a facilitating action of Cplx3/4 on Ca-dependent tonic and evoked neurotransmitter release, respectively, and a regulatory role in the adaptation-dependent availability of synaptic vesicles for release at photoreceptor ribbon synapses.